THE EFFECT OF COMPENSATION AND MOTIVATION ON THE PERFORMANCE OF TEACHING STAFF IN HIGHER EDUCATION - Maria Atriani Mulyati Nanjem; Tutik Winarsih (Transpublika Publisher, 2025)
This study aims to examine the influence of compensation and motivation on the performance of teaching staff at Sekolah Tinggi Ilmu Ekonomi YAPAN Surabaya (STIE) Yapan Surabaya using a quantitative research approach. The performance of teaching staff is a key factor in ensuring academic excellence, and it is significantly affected by internal factors such as the compensation they receive and their level of motivation. Survey questionnaires were given to full-time faculty members at STIE YAPAN Surabaya in order to gather data. An investigation was conducted utilizing multiple linear regression to assess how compensation and motivation impact teaching effectiveness independently and together. The findings indicated that both compensation and motivation play a crucial role in enhancing teaching performance, showing a positive and substantial impact when considered separately as well as together. These findings suggest that improving financial rewards and enhancing motivational support can lead to better performance among academic staff. This research provides valuable input for higher education management in developing effective strategies to improve the quality and productivity of educators.